Cost-effectiveness of olaparib maintenance therapy when used with and without restriction by BRCA1/2 mutation status for platinum-sensitive relapsed ovarian cancer. (4th May 2021) - Cheng, Li-Jen; Wong, Grace; Chay, Wen-Yee; Ngeow, Joanne; Tan, Yongqiang; Soon, Swee Sung; Aziz, Mohamed Ismail Abdul; Pearce, Fiona; Ng, Kwong
ABSTRACT: Objectives : To determine whether olaparib maintenance therapy, used with and without restriction by BRCA1/2 mutation status, is cost-effective at the population level for platinum-sensitive relapsed ovarian cancer in Singapore. Methods : A partitioned survival model compared three management strategies: 1) treat all patients with olaparib; 2) test for germline BRCA1/2 mutation, followed by targeted olaparib use in mutation carriers only; 3) observe all patients. Mature overall survival (OS) data from Study 19 and a 15-year time horizon were used and direct medical costs were applied. Sensitivity analyses were conducted to explore uncertainties. Results : Treating all patients with olaparib was the most costly and effective strategy, followed by targeted olaparib use, and observation of all patients. Base-case incremental cost-effectiveness ratios (ICERs) for all-olaparib and targeted use strategies were SGD133, 394 (USD100, 926) and SGD115, 736 (USD87, 566) per quality-adjusted life year (QALY) gained, respectively, compared to observation. ICERs were most sensitive to the cost of olaparib, time horizon and discount rate for outcomes. When these parameters were varied, ICERs remained above SGD92, 000 (USD69, 607)/QALY. Conclusions : At the current price, olaparib is not cost-effective when used with or without restriction by BRCA1/2 mutation status in Singapore, despite taking into account potential OS improvement over a long time horizon.